Examples:
 Expand, (x + 2y)^{2}.
Given that, (x + 2y)^{2}, this is in the form of (a + b)^{2} = a^{2} + 2ab + b^{2}.
Using above formula,
(x + 2y)^{2} = x^{2} + 4xy + y^{2}
 Expand, (2x  3y)^{2}.
Given that, (2x  3y)^{2}, this is in the form of (a  b)^{2} = a^{2}  2ab + b^{2}.
Using above formula,
(2x  3y)^{2} = 4x^{2}  12xy + 9y^{2}
 Expand,(3x  4y) * (3x + 4y).
Given that, (3x  4y) * (3x + 4y), this is in the form of (a + b)(a  b) = a^{2}  b^{2}.
Using above formula,
(3x  4y) * (3x + 4y) = (3x)^{2}  (4y)^{2}
= 9x^{2}  16y^{2}
Directions: Solve the following problems. Also write at least 10 examples of your own.
